(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
In the service development life cycle it is worthwhile to distinguish between a conceptual phase, that leads to model abstract services, and a production phase that produces concrete services. Both abstract and concrete services produced by a provider organization can be organized, for reuse purposes, in structured repositories of services. As occurs in database design for conceptual schemas, in a single provider organization several repositories of services may coexist, potentially characterized by heterogeneities and conflicting representations. In this paper we present an experience of integration of repositories of abstract services, based on a methodology currently under development.